(untitled) (Global Journals of Research in Engineering, 2020)
In many developing countries, infrastructure development projects are not sustainable due to land valuation conflicts. Mostly, land valuers have assessed land value based on their experiences and without inference. They carry out the subjective land valuation. The detailed spatial analysis of the parcel is not considered for land valuation. The main objective of this study is to analyze the use of GIS in land valuation for land acquisition in infrastructure development. The study is carried out by a literature review with secondary data and primary data. The result shows that adopting GIS for land valuation is necessary and very important for establishing a realistic land valuation system. The model uses various criteria for weighted land valuation and follows an analytical hierarchical process.